2005
DOI: 10.1007/s00018-005-5512-6
|View full text |Cite
|
Sign up to set email alerts
|

Role of the conserved glutamine 291 in the rat γ-aminobutyric acid transporter rGAT-1

Abstract: Abstract. We investigated the role of the Q291 glutamine residue in the functioning of the rat g-aminobutyric acid (GABA) transporter GAT-1. Q291 mutants cannot transport GABA or give rise to transient, leak and transportcoupled currents even though they are targeted to the plasma membrane. Coexpression experiments of wildtype and Q291 mutants suggest that GAT-1 is a functional monomer though it requires oligomeric assembly for membrane insertion. We determined the accessibility of Q291 by investigating the im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
22
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 60 publications
4
22
0
Order By: Relevance
“…2, gray bars), in full agreement with an earlier study (20). This loss of activity is not due to decreased steady-state levels of the mutant transporters on the plasma membrane relative to WT, because the intensity of the bands in the biotinylated fraction of these and almost all of the other mutants studied is similar to that of WT as shown by surface biotinylation (Table 1 and supplemental Fig.…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…2, gray bars), in full agreement with an earlier study (20). This loss of activity is not due to decreased steady-state levels of the mutant transporters on the plasma membrane relative to WT, because the intensity of the bands in the biotinylated fraction of these and almost all of the other mutants studied is similar to that of WT as shown by surface biotinylation (Table 1 and supplemental Fig.…”
Section: Resultssupporting
confidence: 89%
“…Because several of the homologous residues are critical for transport in GAT-1 (16 -19), it is likely that the formation of the thin gate is an obligate intermediate during substrate translocation: the transition from the outward-facing conformation to the inward-facing conformation. A highly conserved glutamine residue, Gln-291 in GAT-1 (Gln-250 in LeuT), has been reported to be crucial for GABA transport by GAT-1 (20). Inspection of the LeuT structure and the putative chloride-binding site suggests two possible reasons why this residue is crucial for transport: 1) hydrogen bond formation with the conserved arginine residue; Arg-69 in GAT-1 (Arg-30 in LeuT), is critical for the formation of the thin gate; and 2) direct interaction with the cotransported chloride predicted by one model (5) (Fig.…”
mentioning
confidence: 99%
“…Figure 10 also shows that the reducing agent DTT (12 mM), after treatment with 0.2 mM CuPh, significantly restored the activity of the K102C/D338C mutant. Recent studies have indicated that members of the NSS family form constitutive oligomers (12,13,15,17,19,20,31,32), although the physiological meaning of this process is still under investigation (17,25,33,35,37). Since KAAT1 belongs to the NSS family, we also considered the hypothesis that CuPh may actually cause the creation of a disulfide bond between two cysteines in different subunits of a KAAT1 homo-oligomer.…”
Section: Amino Acid Uptake When Expressed In Xenopus Laevismentioning
confidence: 99%
“…eral of the homologous residues are critical for transport in GAT-1 (12)(13)(14)(15)(16)(17), it is likely that the formation of the thin gate is an obligate intermediate during substrate translocation: the transition from the outward-to the inward-facing conformation. We have recently shown that perturbation of this thin gate of GAT-1 by mutation increases the proportion of outwardfacing transporters (6).…”
mentioning
confidence: 99%